Measuring the development of Perintis Scholarship beneficiaries based on the Zakat Utilization Index (IPZ) at Rumah Amal Salman / Yedi Purwanto … [et al.] - Purwanto, Yedi; Fitriani, Alfiyah Nur; Aziz, Abdul; -, Syachrial (2023)
Perintis Scholarship is a productive zakat utilization program in the form of college entrance guidance, tuition fees and living expenses during college for poor 3rd grade high school students organized by Rumah Amal Salman. The Perintis Scholarship has been running since 2018 with various updates in terms of methods and resource optimization. This study aims to measure the effectiveness of the perintis scholarship program based on the Zakat Utilization Index (IPZ). The research method is quantitative using IPZ equipped with validity and reliability tests using Ms. Office tools. Questionnaires and surveys were distributed to 84 perintis scholarship recipients from 2021-2023. There are 5 IPZ components that become benchmarks, namely social, cultural, economic, da'wah and environmental. Based on the results of the analysis and calculations, it shows that the perintis scholarship has an IPZ value of 0.69 which falls into the good enough category, meaning that the programme is in the strengthening phase so it needs to be evaluated and improved. Suggestions to improve the effectiveness of the programme need to be strengthened from the social, economic and environmental dimensions so that scholarship recipients are more superior.